A277 CHARACTERISTICS OF PEDIATRIC IBD AT DIAGNOSIS ASSOCIATED WITH SUBSEQUENT USE OF BIOLOGIC THERAPY: A RETROSPECTIVE STUDY. (1st March 2018) - Mulder, D J; Zachos, M; Sherlock, M
Abstract: Background: Inflammatory bowel disease (IBD) is a heterogeneous group of idiopathic conditions commonly treated with increasingly potent anti-inflammatory and immunomodulator medications. The most efficacious medications currently available are biologic agents (TNF-α antagonists). Limited evidence exists to guide the decision to start biologic therapy. Identification of risk factors at presentation that are associated with the eventual use of biologics could be useful for facilitating earlier treatment decisions. Aims: To identify the clinical, biochemical, and radiographic characteristics of IBD at diagnosis associated with subsequent use of biologic therapy. Methods: Charts of all IBD patients actively followed at our centre were reviewed. Data pertaining to clinical, biochemical, and radiologic characteristics at diagnosis were extracted. Disease activity was described using the Pediatric Crohn's Disease Activity Index (PCDAI) and the Pediatric Ulcerative Colitis Activity Index (PUCAI). Therapeutic course was also reviewed, including the timing of immunomodulator and/or biologic therapy initiation. Analyses were performed using SPSS version 21. Results: 218 patients with IBD were identified, 124 (57%) with Crohn's disease, 61 (28%) with ulcerative colitis and 33 (15%) with IBD-type unclassified. 122 (56%) patients received biologic treatment. Time to biologic use was negatively associated with disease activity index at diagnosis for both Crohn's disease (R 2 =0.06, P=0.024) and ulcerative colitis (R 2 =0.33, P<0.002). For all patient groups, binary logistic regression demonstrated that lower height percentile, decreased albumin, and increased CRP at diagnosis (Nagelkerke R 2 =0.29) were associated with biologic use. Receiving biologics within nine months of diagnosis was associated by multivariate logistic regression with lower height percentile, decreased albumin and increased age at time of diagnosis. (Nagelkerke R 2 =0.22). Conclusions: In our cohort, we identified patient characteristics at the time of IBD diagnosis, which were associated with early use of biologic therapy. Further prospective evaluation will help to determine if initiation of biologics based on patient characteristics at the time of IBD diagnosis leads to improved outcomes. Funding Agencies: Regional Medical Associates Scholarship